Chemical and mineralogical forms of heavy metals in sediments at Langat River, Selangor - Shafie, Nur Aliaa (2013)
Langat River is one of the most important rivers in Selangor that caters drinking water sources for up to 1.2 million populations within the basin. In 2004, Langat River has been recognized as one of the Hydrology for the Environment, Life and Policy (HELP) river basin. An explanatory study was carried out at 22 sampling stations along the river. The sediment samples (0 – 20cm) were collected for metal speciation (Cd, Cu, Zn, As, Pb) using sequential extraction technique (SET) and analyzed via the inductively coupled plasma-mass spectrometry (ICP-MS). Parameters such as pH, Eh, electrical conductivity (EC), salinity, loss on ignition (LOI), cation exchange capacity (CEC) and particle size analysis (PSA) were also determined. The sediment mineralogy was determined using X - Ray diffraction (XRD). This study revealed that sediment was predominantly by Pb(150.29μg/g)>Cu(57.91μg/g)>As (37.40μg/g)>Zn (30.46μg/g)>Cd (0.061μg/g). There is a significant correlation among pH, Eh, EC, Ca2+, Cu, Zn, As with Pb at r=-0.234 - 0.354 (p<0.01). The associations among metals (Cd, Cu, Zn and As) © COPYRIGHT UPM ii with sediment characteristics variables were due to the factor that each variables poses towards the bioavailability of metals in the environment. The sediment mineralogy also played a significant role in controlling the fate of metal. The mineralogy that is dominant by quartz correlated with Zn, As and Pb at p<0.1 confirmed that mineralogy controlled the metals accumulation. The fractionation indicate the metals mobility were Cu>Cd>Zn>As>Pb in decreasing order. The association of Cu (94.61%) and Cd (64.80%) were described to be strongly attached with the non residual phase. This is contradicting with Zn (52.46%), As (66.43%) and Pb (92.21%) that accounted as the least mobile metals as a result of strong association with the residual phases. This suggests that Cu and Cd are more prone to the remobilization in the overlying water compared to Zn, As and Pb. The principal component analysis (PCA) exhibited salinity as the controlling factor in the river clusters separation. This is proven by the correlation of salinity with CEC, LOI, Na+, Ca2+, Mg2+, K+, Cd, Cu and Zn at PC1. This suggests that natural sources are the highest percentage of contribution (31.92%). The dendogram displayed stations LA 2, LA 3, LA 4, LA 5 and LA 8 as highly contaminated by Cu, Zn and As. This is supported by sediment quality guidelines (SQGs) that exhibited As as the most contaminated with 100% exceeding the permissible limits. Therefore, it is crucial to understand the interactions of specific metals in the sediment in order to controls the release, remobilization and absorption. These findings are expected to update the current status of the heavy metal pollution status as well as creating awareness concerning the security of the river water as a drinking water sources.